Sistematização da Assistência de Enfermagem: acidente por Loxosceles gaucho. - Kamimura, Helayne Mika; Paiva, Bianca Sakamoto Ribeiro; Ayres, Jairo Aparecido [UNESP] (FapUNIFESP (SciELO), 2009)
Experience report carried out at a university hospital involving a patient victimized by an accident with a spider of the Loxosceles gaucho genus. This type of accident can be classified as mild, moderate and severe, depending on the period of time elapsed between the occurrence of the accident and the moment of care provision. We aimed at applying nursing care systematization in a comprehensive and humanized manner. The following nursing diagnoses were established: acute pain, damaged skin integrity, risks for infection, constipation and low self-esteem. The therapeutic relationship favored student/patient interactions and enabled the recognition of the needs that deserved nursing interventions. The nursing process was a valuable instrument and provided important elements for the patient's daily development and planning adjustment by prioritizing care quality.
Nursing Care Sistematization: accident by Loxosceles gaucho
Keywords: aged; case report; female; human; nursing; nursing care; spider bite; standard; Aged; Arachnidism; Female; Humans; Nursing Care